2010
DOI: 10.1021/nn101884p
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self-Assembly Driven by Electrostatic Repulsion: The 1D Aggregation of Rubrene Pentagons on Au(111)

Abstract: At present, organic molecules are among the best candidate "building blocks" for the construction of self-assembling nanoscale devices based on metal substrates. Control of the formation of specific patterns in the submonolayer regime is usually achieved by appropriate choice and/or functionalization of the adsorbates. The effect of this intervention, though, is limited by the typically short-range character of the bonding. We present here a theoretical study on the system rubrene/gold to show that substrate-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 30 publications
6
55
0
Order By: Relevance
“…An interaction driven by a charge transfer from/to the substrate can be the origin of the repulsion between the chains, as already reported for other one dimensional molecular systems. 25,[48][49][50] A surface state mediated interaction, observed for different adatoms on Cu(111) 51,52 or for pentacene molecules on Cu(110), 53 seems not to be pertinent here, since we find a coverage-dependent average distance between the chains.…”
Section: Resultsmentioning
confidence: 70%
“…An interaction driven by a charge transfer from/to the substrate can be the origin of the repulsion between the chains, as already reported for other one dimensional molecular systems. 25,[48][49][50] A surface state mediated interaction, observed for different adatoms on Cu(111) 51,52 or for pentacene molecules on Cu(110), 53 seems not to be pertinent here, since we find a coverage-dependent average distance between the chains.…”
Section: Resultsmentioning
confidence: 70%
“…[54] In the present case, a possible explanation for the formation of the low-coverage self-assembled phases (and specifically of the chains of pentagonal supermolecules) is charge transfer from the highest occupied molecular orbital to the gold surface, leading to the formation of dipoles. [23,55] As a consequence, short-range attractive intermolecular forces compete with long-range repulsive forces due to dipolar interactions, and this leads to the observed formation of dispersed assemblies. This process is determined by the specific relation between the work function of gold and the electronic structure of rubrene.…”
Section: Discussionmentioning
confidence: 99%
“…[22] However, recently, (sub)monolayers of rubrene on Au (111) are reported to formdepending on the specific preparation conditions-manifold supramolecular structures of essentially flat lying molecules as evidenced by scanning tunneling microscopy (STM). [23][24][25][26] Con sequently, the mutual supramolecular stabilization might lead to a conformational transition on a shorter length scale or even to the concomitant occurrence of rubrene in a twisted and a planar conformation in the monolayer on Au (111) or other inert substrates like graphite. In a recent STM study of rubrene on Bi (001) such a coexistence was actually experimentally shown for monolayer coverage.…”
Section: Doi: 101002/adma201103262mentioning
confidence: 99%